Systemic antimicrobials adjuvant to periodontal therapy in diabetic subjects: a meta-analysis - Grellmann, Alessandra Pascotini; Sfreddo, Camila Silveira; Maier, Juliana; Lenzi, Tathiane Larissa; Zanatta, Fabricio Batistin (Journal of clinical periodontology, 2016)
Background Adjuvant antibiotics have been suggested to improve periodontal therapy in diabetic subjects. Aim The aim of this study was to systematically review randomized clinical trials assessing systemic antimicrobial use adjuvant to scaling and root planing (SRP) versus SRP alone in diabetic subjects. Material and Methods The PubMed, Cochrane Central Register of Controlled Trials, EMBASE, TRIP, Web of Science and LILACS databases and the grey literature were searched through May 2015. Of 2534 potentially eligible studies, 13 were included in the systematic review. Weighted mean differences (WMDs) in probing depth (PD) reduction and clinical attachment level (CAL) gain (primary outcomes), and plaque index (PI) and bleeding on probing (BOP) reductions, were estimated using a random effect model. Results The WMD in PD reduction [−0.15 mm, n = 11, p = 0.001, 95% confidence interval (CI) −0.24, −0.06] favoured antibiotic use. WMDs in CAL gain, PI and BOP reductions (−0.14 mm, n = 9, p = 0.11, 95% CI −0.32, 0.03; 4.01%, n = 7, p = 0.05, 95% CI −0.04, 8.07; and −1.91%, n = 7, p = 0.39, 95% CI −6.32, 2.51 respectively) did not favour adjunctive antibiotic use. Conclusion Adjunctive therapy may improve the efficacy of SRP in reducing PD in diabetic subjects.